Thermodynamics sheds light on the nature of dark matter galactic halos - Aceña, Andrés Esteban (2023)
Today it is understood that our universe would not be the same without dark matter, which apparently has given rise to the formation of galaxies, stars and planets. Its existence is inferred mainly from the gravitational effect on the rotation curves of stars in spiral galaxies. The nature of dark matter remains unknown. Here we show that the dark matter halo is in a state of Bose-Einstein condensation, or at least the central region is. By using fittings of observational data, we can put an upper bound on the dark matter particle mass in the order of 12 eV/c2. We present the temperature profiles of galactic dark matter halos by considering that dark matter can be treated as a classical ideal gas, as an ideal Fermi gas, or as an ideal Bose gas. The only free parameter in the matter model is the mass of the dark matter particle. We obtain the temperature profiles by using the rotational velocity profile proposed by Persic, Salucci, and Stel (1996) and assuming that the dark matter halo is a self-gravitating stand-alone structure. From the temperature profiles, we conclude that the classical ideal gas and the ideal Fermi gas are not viable explanations for dark matter, while the ideal Bose gas is if the mass of the particle is low enough. If we take into account the relationship presented by Kormendy and Freeman (2004, 2016), Donato et al. (2009) and Gentile et al. (2009) between central density and core radius then we conclude that the central temperature of dark matter in all galaxies is the same. Remarkably, our results imply that basics thermodynamics principles could shed light on the mysterious nature of dark matter and if this is the case, those principles have to been taken into account in its description.